2008
DOI: 10.1007/s00405-008-0830-6
|View full text |Cite
|
Sign up to set email alerts
|

Histologic and morphologic evaluation of explanted bone anchors from bone-anchored hearing aids

Abstract: Bone-anchored hearing aids are a standard option in rehabilitation of patients with conductive or mixed hearing loss, and also CROS fitting. However, the skin-penetrating bone anchor repeatedly gives reason for discussion about the risk of infection of surrounding tissues as a major cause of malfunction. In the present study, explanted bone anchors with surrounding bone and soft tissue were examined and compared with the morphology of lost implants. The anchors originated from five patients. Two needed explant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…In the Mlynski and colleagues' series, one of the five patients who required removal of their BAHA implant had experienced intractable pain; in this patient, computed tomography demonstrated contact between the implant and the underlying sigmoid sinus dura 20 . Mlynski et al and Granstrom demonstrated similar degrees of bone–metal contact, which tended to increase with increasing loading times; however, neither showed any relationship with chronic pain symptoms 20 , 21 …”
Section: Discussionmentioning
confidence: 89%
“…In the Mlynski and colleagues' series, one of the five patients who required removal of their BAHA implant had experienced intractable pain; in this patient, computed tomography demonstrated contact between the implant and the underlying sigmoid sinus dura 20 . Mlynski et al and Granstrom demonstrated similar degrees of bone–metal contact, which tended to increase with increasing loading times; however, neither showed any relationship with chronic pain symptoms 20 , 21 …”
Section: Discussionmentioning
confidence: 89%
“…They concluded that there was no viable attachment in any of the titanium abutments studied. Mlynski et al ( 33 ) also concluded that soft tissue does not attach tightly to the titanium bone conduction hearing implant abutment. Their histological results showed no signs of skin integration.…”
Section: Discussionmentioning
confidence: 99%
“…Three implants, one spontaneous loss and two from elective removal were analyzed using scanning electron microscopy. The ultrastructural interaction between the surrounding bone as well as osteocyte processes attaching to the implant surface for the two electively removed implants was demonstrated; however, none of these features were present in the extruded implant (Mlynski et al, 2008). Nine of the ten implants inserted in the volunteers were removed using a torque gauge instrument after 3-4 months, with a mean removal torque of 42.7 Ncm (range 26 to 60 Ncm) (Tjellstrom et al, 1988).…”
Section: Synthesis Of Results From Literature Reviewmentioning
confidence: 99%
“…After independently reading the full-text (authors MLJ and AP), 6 articles fulfilled the inclusion criteria and were selected for inclusion. The manual search and screening of reference lists resulted in the further addition of 4 articles leading to a total of 10 articles, published between 1987 and 2008, to be included in the review (Jacobsson et al, 1987;Tjellstrom et al, 1988;Holgers et al, 1994a;van der Pouw et al, 1998;Bolind et al, 2000;Granström, 2000;Mylanus et al, 2002;Bolind et al, 2006;Khwaja et al, 2008;Mlynski et al, 2008).…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation